AN ANALYSIS OF MORAL AND EDUCATIONAL VALUES ON MADURA FOLK SONGS - Abdul Wakil (JURNAL ILMIAH BAHASA DAN SASTRA, 2015)
At this moment traditional songs was not pay attention so that almost the traditional song is not well known by young generations. The position of traditional songs was lost with technology. If there is not an conservation and appreciation for traditional songs especially Madura traditional songs, so the traditional song can be lost in the future so that writer try to analysis of moral and educational values on Madura folk songs. The discussion in this thesis the author tried to review the pedagogical values particularly with regard to the morality contained in the lyrics of Madura folk song. The author only took eight songs contained in a book of poetry titled Madura folk songs "set song Madura Regions" in 2003 by the author R. Amirudin Tjitraprawira Namely; “Lir Saalir”, “Tondu’ Majang”, “Pajjhar Langgu”, “Caca Aghuna”, “Pa’-Opa’ Iliing”, “Pacakang Alako”, “Entar Akarang”, “Les Balesan”. The research was conducted with the following statement of problems: (1) What are moral and educational values found on Madura folk song by R. Tjitraprawira? (2) How is the meaning of Madurese life which is contained in the Madura song lyric? (3) What are the messages that can be delivered to the reader on Madura folk song by R.Amiruddin Tjitraprawira? The objective of this study was to know moral value found on madura folk song, to know how the meaning of madurese life which is contained in the madura song lyric,to know the message that can be delivered to the reader of madura folk song by R.Amiruddin Tjitraprawira. The researcher uses descriptive qualitative approach in finding moral and educational values. The research method is used from the researcher itself because for analysis the data use interpretation of own words. The data is taken eight titles from Madura songs such as “Lir Saalir”, “Tondu’ Majang”, “Pajjhar Langgu”, “Caca Aghuna”, “Pa’-Opa’ Iliing”, “Pacakang Alako”, “Entar Akarang”, “Les Balesan”. The researcher choose this titles because it contains the high valuable meaning related Madura daily activities which is designed in madurese language. Finally, this study uses semantic as the base theory which related on moral and educational values. Therefore, the researcher suggests to the next researcher whom want concern with the similar topic to analyze moral and educational values should be attention the theory which accordance with the research object itself and look for references that can be found in journal, newspaper, and books, etc.